1960
DOI: 10.1172/jci104109
|View full text |Cite
|
Sign up to set email alerts
|

Strontium and Calcium Metabolism in Metabolic Bone Diseases *

Abstract: Skeletal and systemic disease may be reflected in profound alterations of the metabolism of the bone salts. In human skeletal disease attention has focused, for the most part, on the altered metabolism of calcium. Several studies indicate that strontium may have a metabolic pathway similar to that of calcium and that radiostrontium, because of its ease of measurement, might be a convenient indicator for observing the transfer of calcium through the calcium-containing compartments of the body.The investigations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
2

Year Published

1961
1961
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 18 publications
2
38
1
2
Order By: Relevance
“…Equation 5 applies as well, but absorption is also defined by Va = Vi + Vd -VF, [9] and the fraction absorbed becomes a = Va/ (Vi + Vd). [10] Equations 8, 9, and 10 are based on the assumption that vi and Vd are absorbed to the same extent and therefore presumably are thoroughly mixed (1).…”
Section: Definitions and Notationmentioning
confidence: 99%
“…Equation 5 applies as well, but absorption is also defined by Va = Vi + Vd -VF, [9] and the fraction absorbed becomes a = Va/ (Vi + Vd). [10] Equations 8, 9, and 10 are based on the assumption that vi and Vd are absorbed to the same extent and therefore presumably are thoroughly mixed (1).…”
Section: Definitions and Notationmentioning
confidence: 99%
“…[13] In a system without central pool of constant size, this specific activity remains constant throughout the experiment. By combining Equations 12 and 13, one obtains the amount of radioactivity, R, circulating at time t: R = Ri MOe-(ku+kf+ko+)t = Rie-(ku+kf+ko+)t [14] If RB is the amount of circulating radioactivity per unit of plasma volume, the time-course of this parameter can be expressed in terms of Equation 14 as follows: [15] where L = total apparent volume of distribution of the circulating mass ( [18] 1098 E10] 2 If the experimental error is 5%, the absolute error for the mean urine excretion of Ca45 (Table III) is 0.80 (0.05 X 16) and for fecal excretion of Ca450.70 (0.05 X 14). The error for the total excretion is therefore 1.5, which necessarily is the same absolute error for the percentage of dose in bone [100 -(14 + 16)].…”
Section: Methodsmentioning
confidence: 99%
“…Early experiments (1)(2)(3) confirmed this notion in a general way, and several investigators (4)(5)(6)(7) have subsequently proceeded on the assumption that Sr behaves like Ca in the body. Although the urinary excretions of Sr and Ca were found to differ, it has been assumed or demonstrated that as far as the skeleton is concerned, differences in the biological behavior of Ca and Sr are small and perhaps negligible (4,(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…This lower uptake may be a reflection of the emotional stress observed in these monkeys during intubation, and which Malm (26) considered to be a factor in human subjects. 4. Urine: feces ratios of Ca45 excretion.…”
Section: Methodsmentioning
confidence: 99%
“…Data obtained on patients with carcinoma, multiple myeloma, and thyroid disorders indicate that the excretion of Ca45 is disturbed in these situations, for the urine: feces excretion *A portion of this paper was presented at the Fifth International Congress on Nutrition, Washington, D. C., September 1, 1960. This study was ratios ranged between 3:1 and 1: 3 (3)(4)(5)(6). In spite of these anomalies, the "endogenous" excretion of calcium by normal human beings and normal monkeys appears to be similar, and quite unlike that by the dog and the rat.…”
mentioning
confidence: 98%